ENGLISH TEACHERS’ STRATEGIES IN DEVELOPING READING MATERIALS FOR YEAR TEN STUDENTS AT SMA NEGERI 1 BARRU - Muhammad Khalil Gibran Rusdi; Chairil Anwar Korompot; Sahril Nur (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This study aims to find out the teacher's strategies and the obstacles faced by the teacher in teaching reading in particular. This study used the descriptive qualitative method. Data were collected from interviews with video and audio recorders. Data were taken from English teachers at SMA 1 Barru. The results of this study indicate that the strategy teachers use more is the reading aloud strategy and sometimes also the estapet reading in teaching reading. The goal is the same, namely by focusing and mentally training students so that they can focus on the reading material that the teacher provides in teaching reading, while there are several obstacles related to teacher complaints regarding student pronunciation in teaching reading in class X, although it still can be said to be reasonable because they are in the transition process from junior high school to high school. Also, the student’s English levels are different. Therefore, the teacher should make the students more proactive in learning reading in particular.